2015
DOI: 10.1002/mc.22413
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of nitrogen permease regulator like‐2 activates PDK1‐AKT1 and contributes to the malignant growth of glioma cells

Abstract: Nitrogen permease regulator like-2(NPRL2) is a candidate tumor suppressor gene(TSG) located on chromosome 3p21.3 and deletions frequently occur in this region, leading to canceration. Recently, molecular pathologic researches have provided valuable insights into the downregulation of NPRL2 in carcinogenesis in some types of cancers. However, very little is known about genetic changes of NPRL2 involved in glioma. Here, for the first time, we aimed to understand the expression levels, functions and mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Food and water were sterilized by high pressure steam and multivitamins were added into distilled water. The subcutaneous tumor model was produced as previously described ( 18 ). For treatment, 5 mg/kg DOX alone or 5 mg/kg DOX + 5 mg/kg/day TFP was injected the tail vein (DOX every 7 days and TFP every day).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food and water were sterilized by high pressure steam and multivitamins were added into distilled water. The subcutaneous tumor model was produced as previously described ( 18 ). For treatment, 5 mg/kg DOX alone or 5 mg/kg DOX + 5 mg/kg/day TFP was injected the tail vein (DOX every 7 days and TFP every day).…”
Section: Methodsmentioning
confidence: 99%
“…For treatment, 5 mg/kg DOX alone or 5 mg/kg DOX + 5 mg/kg/day TFP was injected the tail vein (DOX every 7 days and TFP every day). Tumor volumes were recorded at 7, 14, 21 and 28 days post-implantation in accordance with the previously described formula ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lohneis et al 12 also pointed that PDK1 was an independent prognostic factor that is significantly negatively correlated to tumor grade in ovarian serous carcinoma. Moreover, other studies proved that PDK1 was correlated to prognosis of malignant gliomas, 13 breast cancer, 14 , 15 gall bladder cancer, 16 colorectal cancer, 17 and pancreatic cancer. 18 However, the relationship between PDK1 expression and prognosis of HCC has not yet been explored.…”
Section: Discussionmentioning
confidence: 96%
“…NPRL2 expression level was negatively correlated with the survival rate of patients with osteosarcoma and hepatocellular carcinoma (HCC), indicating its value as an independent prognostic marker [ 12 , 13 ]. Furthermore, intratumoral injection of a recombinant adenoviral or lentiviral vector containing NPRL2 gene significantly suppressed tumor growth and tumor progression and metastasis in various human lung cancer and glioma mouse models [ 10 , 14 ]. A prior evaluation revealed that NPRL2, as a molecular therapeutic target for enhancing and resensitizing the reaction to cisplatin, has been documented in lung cancer [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs, in particular MMP2 and MMP9, are critical to tumor cell movement and invasion [ 26 ]. Huang et al documented that the down-regulation of NPRL2 stimulates PDK1-Akt1 and adds to the malignant development of glioma cells [ 14 ]. The PI3K/AKT pathway is a crucial signaling pathway that is responsible for cancer migration and invasion [ 27 ].…”
Section: Discussionmentioning
confidence: 99%